HISTORICAL AND LEGAL ORIGINS OF MODERN UKRAINIAN CONSTITUTIONALISM - Holovko, Svitlana; Varava, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to characterize the historical and legal origins, sources of formation and directions of development of the constitutional process in Ukraine. Methods: using the method of historical and legal analysis outlines the prerequisites for the formation of domestic constitutionalism as a phenomenon of state formation; the method of comparative analysis was used to substantiate the impact on the development of the constitutional process in Ukraine of the traditions of European constitutionalism and the progressiveness of modern trends in its development; using the method of synthesis, the interdependence of the sources of formation and tendencies of development of Ukrainian constitutionalism is determined. Results: the need to improve the mechanism of constitutional regulation of public relations taking into account the historical and legal origins of the constitutional process; it is substantiated that the sources of Ukrainian constitutionalism are the achievements of European constitutional thought and domestic centuries-old historical and legal traditions that provide a relatively independent character, a variety of trends in the constitutional process (from globalism to regionalism); the main directions and topical issues of development of modern constitutional and legal support in Ukraine are determined; concluded that an important condition for the formation of the Ukrainian democratic, legal and social state is the proper theoretical support of the process of national constitutional law, taking into account the world, European and domestic experience of constitutionalism; Emphasis is placed on the socio-legal preconditions of constitutionalism as an effective mechanism for ensuring and protecting the constitutional order, human and civil rights and freedoms, in particular, the improvement of local self-government as an effective institution of civil society. Discussion: effective mechanisms for the implementation of constitutionalism and its development on the basis of European and domestic traditions of the constitutional process.